Threshold Concepts in Radiation Physics Underpinning Professional Practice in Radiation Therapy - Hudson, Lizel; Engel-Hills, Penelope; Winberg, Christine (International Journal of Practice-based Learning in Health and Social Care, 2018)
This article identifies potential threshold concepts in radiation physics, and explains their relationship to professional practice in radiation therapy (that is,. the practice of radiation treatment and care of cancer patients). Concepts such as how the radiation beam spreads out (beam divergence), and how the distance from the ionising source affects the beam (inverse-square law), can be challenging for students entering higher education and experiencing their first clinical placements. Through observations of radiation therapy students in practice, mastery of these (and other concepts) appears essential for them to progress in their professional practice learning. The study used ‘transactional curriculum inquiry’ (Cousin 2009) in order to understand why particular concepts might be troublesome to students, and how mastery of these concepts could potentially lead to safe and accurate practice. While the study was conducted in a particular Bachelor of Science in Radiation Therapy programme, it has implications for how academic and clinical educators in other contexts might facilitate students’ acquisition of the threshold concepts that underpin professional practice. The findings suggest that the typical progression in professional education that assumes the application of theoretical concepts to practice, might not be the best way to acquire the threshold concepts that lead to transformed practice.